Examining the Availability of Physical Education Facilities and Teacher Innovation in Equipment Modification in Junior High Schools - Cici Maharani Katala; Nargiza Pirimova; Himmat Eshboyev (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to identify the availability, quality, and utilization of Physical Education, Sports, and Health facilities and infrastructure in public junior high schools in Purbalingga, and to examine teacher creativity in modifying learning tools to overcome facility limitations. Methodology: This study employed a qualitative descriptive design using observation, documentation, and questionnaire techniques. Data were collected from public junior high schools in Purbalingga. Instruments included observation sheets and questionnaires for teachers. Data analysis was conducted through data reduction, data display, and conclusion drawing based on percentage standards. Main Findings: The results show that the availability of facilities is generally categorized as fairly ideal to ideal, although disparities exist among schools. Some facilities are in poor condition and not optimally utilized. Teacher creativity in modifying equipment using simple materials was identified as an effective strategy to support learning. Novelty/Originality of this study: This study provides a comprehensive regional analysis of facilities combined with an examination of teacher creativity in modifying learning tools. It offers a more integrated perspective by linking facility availability with adaptive teaching practices in resource-limited school environments.